2022
DOI: 10.1063/5.0082583
|View full text |Cite
|
Sign up to set email alerts
|

Cluster perturbation theory. VI. Ground-state energy series using the Lagrangian

Abstract: In this paper, we derive alternative cluster perturbation series to the energy cluster perturbation (ECP) series of Paper I. The ECP series were derived using the standard coupled cluster energy framework. Here, we use the coupled cluster Lagrangian framework to derive the Lagrangian cluster perturbation (LCP) series and show that a slightly modified order concept means that the ECP and the LCP series become identical. Using the Lagrangian, we also derive a perturbation series where total cluster amplitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We have performed a small control investigation by selecting three molecules with the best xTB predicted properties, and three molecules with the worst xTB predicted properties. We have compared the xTB and DFT results for these six molecules with calculations performed at a higher-level of theory, namely, the variational method 49 for single point energies and excitation energy calculations using the CPS(D-3) model 50,51 on the DFT optimized geometries. The three best (worst) molecules according to xTB are denoted 1, 2, and 3 (−1, −2, and −3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have performed a small control investigation by selecting three molecules with the best xTB predicted properties, and three molecules with the worst xTB predicted properties. We have compared the xTB and DFT results for these six molecules with calculations performed at a higher-level of theory, namely, the variational method 49 for single point energies and excitation energy calculations using the CPS(D-3) model 50,51 on the DFT optimized geometries. The three best (worst) molecules according to xTB are denoted 1, 2, and 3 (−1, −2, and −3).…”
Section: Resultsmentioning
confidence: 99%
“…The developed screening procedure based on xTB methods can clearly be utilized for designing MOST molecules having optimal properties for actual MOST devices. We observed that molecules that performed the best in the screening procedure were performing extremely well when we utilized accurate quantum mechanical methods such as the variational method 49 and the CPS(D-3) model. 50,51 We also note that recent work reaches similar conclusions concerning the use of TB methods that the methods can be used for screening and designing MOST systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations have been performed in Gaussian16 . This methodology is chosen as earlier studies have shown good performance for both NBD/QC and BOD/TCO systems. , Subsequently, we refine the electronic energy of the determined structures using the newly developed cluster perturbation theory CPS­(D-4) model in LSDalton, ,, which provides energies of CCSD quality at a low cost, while we utilize the vibrational and entropic energy contributions of the DFT calculations. The resulting storage energies are given in Table .…”
Section: Thermochemical Propertiesmentioning
confidence: 99%
“…The result of this is that the error relative to the CCSD energy in the obtained energy is bilinear in the errors of the approximate parameters, while the error obtained in the incremental formulation is linear in the errors of the amplitudes and multipliers. For a detailed derivation and analysis of these energy models, we refer the reader to previous studies 72 that give full derivations of these models.…”
Section: = |[ ]|mentioning
confidence: 99%